Zakat and Poverty Alleviation in a Secular State: The Case of Muslim Minorities in the Philippines - Gamon, Alizaman D.; Tagoranao, Mariam Saidona (Studia Islamika, 2018)
Twelve million Filipinos live in extreme poverty. Despite a well-crafted government model for poverty alleviation, the state’s role in managing charities to alleviate economic deprivation has been minimal. By reason of the state’s strict adherence to secularism, the operation of Islamic institutions at the social level is deemed unconstitutional. It is unfortunate that the dynamics of Islamic social financial institutions, i.e. zakat, waqf and ṣadaqah, are not reflected in the economic road map for the reconstruction of the Autonomous Region in Muslim Mindanao, particularly the rehabilitation of the city of Marawi after the war. This study examines the initiatives taken by government agencies and Muslim organizations towards the gradual revival of zakat as an Islamic social financial institution. In addition, the study highlights issues on the management of zakat and its role in poverty alleviation within the context of a secular state. This study finds that due to mismanagement, zakat fails to eliminate or reduce the poverty of the Muslim minorities in the Philippines.DOI: 10.15408/sdi.v25i1.5969